1
$\begingroup$

Obtain another expression for $(\cos θ + i \sin θ)^4$ by direct multiplication (i.e., expand the bracket). Use the two expressions to show $$ \cos 4\theta = 8 \cos^4 \theta − 8 \cos^2 \theta + 1,\\ \sin 4\theta = 8\cos^3\theta \sin\theta − 4 \cos \theta\sin \theta. $$ You may use the well-known identity: $\sin^2 \theta + \cos^2 \theta = 1$, but do not use any multiple angle formula.

I got using DMT that $(\cos \theta + i\sin \theta)^4 = (cos 4\theta + i\sin 4\theta)$ and using direct multiplication, I got $\cos^4\theta + \sin^4\theta - 4\cos^3\theta*\sin\theta*i - 4\cos\theta \sin^3\theta i - 6\cos^2\theta\sin^2\theta$

$\endgroup$
3
  • 1
    $\begingroup$ ...so...? What did you get? $\endgroup$
    – Timbuc
    Nov 17 '14 at 18:45
  • $\begingroup$ De Moirve's theorem tells us that $(\cos(\theta) + i\sin(\theta))^n = \cos(n\theta) + i\sin(n\theta)$ but your question doesn't say to use but to expand. If you are going to expand, I would recommend using exponentials. $\endgroup$
    – dustin
    Nov 17 '14 at 18:45
  • $\begingroup$ It does. It says to use both ways to show that cos 4θ = 8 cos^4 θ − 8 cos2^ θ + 1. and to also show that sin 4θ = 8 cos^3 θ sin θ − 4 cos θ sin θ. $\endgroup$ Nov 17 '14 at 18:47
1
$\begingroup$

By De Moivre’s theorem, $$ (\cos\theta+i\sin\theta)^4=\cos 4\theta+i\sin 4\theta. $$ On the other hand $$ (a+b)^4=a^4+4a^3b+6a^2b^2+4ab^3+b^4 $$ Expand the binomial and equate the real and imaginary parts. Where you find $\sin^2\theta$, substitute $1-\cos^2\theta$.

You have, almost correctly, $$ \cos4\theta+i\sin4\theta= \cos^4\theta+4i\cos^3\theta\sin\theta+6i^2\cos^2\theta\sin^2\theta +4i^3\cos\theta\sin^3\theta+i^4\sin^4\theta $$ Now $i^2=-1$, $i^3=-i$ and $i^4=1$, so, by equating the real and imaginary parts, we get $$ \cos4\theta=\cos^4\theta-6\cos^2\theta\sin^2\theta+\sin^4\theta\\ \sin4\theta=4\cos^3\theta\sin\theta-4\cos\theta\sin^3\theta $$ Now it's just a matter of substituting $\sin^2\theta=1-\cos^2\theta$, so, for example, we have \begin{align} \sin4\theta&=4\sin\theta(\cos^3\theta-\cos\theta\sin^2\theta)\\ &=4\sin\theta(\cos^3\theta-\cos\theta+\cos^3\theta)\\ &=8\cos^3\theta\sin\theta-4\cos\theta\sin\theta. \end{align} Do similarly for $\cos4\theta$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.